Baicalin reduces chronic stress-induced breast cancer metastasis via directly targeting β2-adrenergic receptor - Qi Jia; Yinyin Zhou; Li Song; Ximeng Shi; Xuan Jiang; Ruizhi Tao; Aiyun Wang; Yuanyuan Wu; Zhonghong Wei; Yinan Zhang; Xiaoman Li; Yin Lu (Elsevier, 2024)
Recent studies have shown that stress can substantially facilitate breast cancer metastasis, which can be reduced by nonselective β1/β2-adrenergic receptor (β1/β2-AR) blocker. However, several side effects were identified. Thus, it is extremely warranted to explore more effective and better-tolerated β2-AR blocker. Currently, we demonstrated that baicalin (BA), a major bioactive component of Scutellaria baicalensis Georgi, could significantly attenuate stress hormones especially epinephrine (Epi)-induced breast cancer cell migration and invasion in vitro. Mechanistically, we identified that β2-AR was a direct target of BA via the drug affinity responsive target stability (DARTS) combined with mass spectrum assay, and BA photoaffinity probe with pull-down assay, which was further confirmed by a couple of biophysical and biochemical assays. Furthermore, we demonstrated that BA could directly bind to the Phe-193 and Phe-289 of β2-AR, subsequently inhibit cyclic adenosine monophosphate-protein kinase A-focal adhesion kinase (cAMP-PKA-FAK) pathway, and thus impede epithelial-mesenchymal transition (EMT), thereby hindering the metastatic progression of the chronic stress coupled with syngeneic and xenograft in vivo orthotopic and tail vein mouse model. These findings firstly identify BA as a potential β2-AR inhibitor in the treatment of stress-induced breast cancer metastasis.